2022
DOI: 10.3389/fpubh.2022.873936
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences for the Prevalence and Risk Factors of Workplace Violence Among Healthcare Professionals in Shandong, China

Abstract: BackgroundWorkplace violence (WPV) against healthcare professionals (HPs) has been recognized as important occupational health and societal problem in the world. Many studies were also conducted to explore the prevalence, risk factors, and adverse outcomes of WPV against HPs. Although the gender differences in the prevalence and risk factors of WPV against HPs have been implied in many studies, fewer studies were conducted to explore the gender differences for WPV against HPs, especially in China. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 56 publications
4
20
0
1
Order By: Relevance
“…In this study, a higher prevalence of PV and VV was reported among doctors and managers, which was also supported in previous studies ( 32 , 47 , 51 ). Doctors need to take charge of the therapeutic plan and frequently communicate with patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, a higher prevalence of PV and VV was reported among doctors and managers, which was also supported in previous studies ( 32 , 47 , 51 ). Doctors need to take charge of the therapeutic plan and frequently communicate with patients.…”
Section: Discussionsupporting
confidence: 92%
“…VV was also recoded as yes (1) or no (0), with the former one including medical staff reporting verbal violence and BV. This question has been used to evaluate WPV in many previous studies ( 32 , 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosptials should equip key departments with one-button alarm devices and increase the intensity of security in high risk areas (39). Additionally, social support is key to mental health and worker wellbeing and should be a focus of hospital remediation efforts to mitigate the effects of unavoidable WPV (40).…”
Section: Practice Implicationmentioning
confidence: 99%
“…Multiple studies from other health workforces have found a higher prevalence of workplace violence among male workers. [43][44][45] The association of workplace violence with older age groups has been shown among nurses in Australia. [44] A recent study from the United States also suggested that older workers experience more severe episodes of physical assault.…”
Section: Workplace Violencementioning
confidence: 99%